PROTOCOLS OF THE INTERNATIONAL LABOR ORGANIZATION AND DOMESTIC LEGAL ORDER - Gunther, Luiz Eduardo; Villatore, Marco Antônio César; Cochran III, Augustus Bonner (Revista Jurídica (FURB), 2021)
The International Labor Organization (ILO), created with the aim of promoting social justice, adopts conventions, which are instruments that establish guidelines for the policy and national actions of its Member States. Because of the changes produced by globalization, sometimes it is necessary to improve and update these conventions. In order to do so, the ILO adopts instruments called protocols, which confer greater flexibility to a convention or extend its obligations. Just as conventions, protocols are also international treaties, and are subject to ratification. They allow for the adaptation to changing conditions and the adjustment to practical difficulties that have arisen since the adoption of the Convention, thus making it more relevant and updated.